The use of a cusp-bearing homograft patch to the outflow tract and pulmonary artery in Fallot's tetralogy and pulmonary valvular stenosis - Marchand, Paul (1967)
A technique is described for maintaining pulmonary valve competence whilst widening the hypoplastic pulmonary artery ring found invariably in Fallot's tetralogy and pulmonary valve stenosis. A homograft composed of the aortic cusps, a portion of ascending aorta, and the anterior mitral leaflet is used. One, two, or three cusps may be replaced or added by variations of technique. The right ventricular outflow tract and the pulmonary trunk are also widened. The operation is applicable to children, and adult homografts can be used. The ring should be widened to a circumference of from 6 to 8 cm. so as to prevent residual pressure gradients. One or two cusp replacements are favoured in the hope that growth will proceed because a continuous portion of natural pulmonary artery and ring remains untouched. An advantage of the technique is the small ventriculotomy required to excise the infundibular obstruction and close the ventricular septal defect. Four case histories are presented. Three patients have survived operation and are doing well. Up to six months post-operatively no serious pulmonary incompetence has developed.